Expression and purification of recombinant DNA endonuclease of CRISPR/Cas system - Amanzholova, M.Zh.; Shaizadinova А.М.; Abeldenov С.К. (Fundamental and Experimental Biology, 2022)
Currently, active research work is underway to study and use site-specific RNA-guided endonucleases as tools for use in the field of genome editing and diagnostics in the biomedical and biotechnological fields. To date, the most effective method in this area is the CRISPR method. Due to its ease of targeting, this system was quickly adopted as the method of choice for editing the genomes of numerous organisms. More recently, another novel CRISPR-Cas class 2 endonuclease with characteristic features has been discovered in bacterial genomes: Cas12a. The Cas12a enzyme is a site-specific RNA-guided endonuclease that can be used for pre-cise genome editing in various cell types of different species, as well as for diagnostic applications. The search, identification and characterization of new unexplored homologues will expand the potential of en-zyme applications. In this work, the expression and two-stage chromatographic purification of the recombi-nant enzyme Cas12a of high purity were carried out. In vitro synthesized crRNA, ribonucleoprotein complex were obtained and by the endonuclease activity of the enzyme in relation to the substrate containing the target sequence for cleavage in the appropriate site was confirmed. The resulting enzyme can be used to further de-scribe its kinetic parameters, which can be applied in the development of new next-generation diagnostics.